THE ROLE OF TEACHERS IN BUILDING ENVIRONMENTAL CARE CHARACTER IN ELEMENTARY SCHOOL STUDENTS THROUGH PROJECT LEARNING AT SDN KOTA KULON VII - Salamah , Rima; Mikkey Anggara Suganda; Syifa Nurbait (Jurnal Ilmu Pendidikan Dasar (JIPDA), 2024)
This research aims to explore the role of teachers in developing environmental care character in elementary school students through project-based learning at SDN Kota Kulon VII. The background of this research is driven by the rapid and dramatic environmental changes that demand younger generations possess a deep understanding and awareness of the importance of environmental preservation. As future agents of change, students need to be equipped with an environmental care character encompassing knowledge, attitudes, and concrete actions for environmental sustainability. This study employs a qualitative approach with a case study method. The research population consists of 5th and 6th-grade students and teachers involved in environmental learning activities. Data collection is conducted through observations, in-depth interviews with teachers and students, and document analysis related to environmental project activities. The research instruments include interview guidelines, observation sheets, and document analysis. Data is analyzed using thematic analysis techniques, involving coding and grouping findings to identify relevant patterns. The research results show that teachers act as guides, motivators, and facilitators in designing and implementing environmental projects such as recycling and tree planting. Teachers also serve as role models for environmentally friendly behavior and collaborate with parents and the community to support environmental activities. Through project-based learning, students not only understand the impact of their actions on the environment but also develop social skills, increase motivation, and build an environmental care character. This research provides significant contributions to the literature on environmental education and the development of sustainable learning practices at the elementary school level.